Adapt or Resist? A Socio-Political Reading of Revelation 2.18-29 - Friedrich, Nestor Paulo (2002)
The letter to the church in Thyatira at Rev. 2.18-29 uses literary conventions of imperial edicts to produce a ‘prophetic edict’ as a means of emphasizing the authority of God as superior to imperial authority. The technique of parodying imperial edicts is paralleled by contemporary marginal groups. An analysis of the letter to Thyatira provides an understanding of the critique by Christians in first-century Asia Minor of the Pax Romana. The prophetic edict to Thyatira shares with chs. 4–22 of Revelation an analysis of the political, economic and religious context. The critique of imperial power is also the basis of a call to fidelity and resistance.